Land suitability assessment of small tea plantations for sustainability using analytical hierarchy process (AHP) technique: a case study of Udalguri district, Assam (India) - Machahary , Jeshmi; Kumar Kar , Bimal; Kreutzmann , Hermann (Acta Geographica Lodziensia, 2025)
Land is one of the most precious natural resources in densely populated regions of the world like India. The everincreasing population and increasing number of small tea growers (STGs) in Assam and the expansion of settlements have caused difficulties for small tea growers in choosing land, as not every land is suitable for tea cultivation. In Udalguri district, 54.13% are low-lying areas, and more than half the population is engaged as farmers in the district. So, finding land very suitable for tea cultivation is difficult and expensive. On the other hand, farmers are expanding in the northern foothills region of Bhutan and even up to the forest region. So, as suitable land is very scarce, people can also grow in some parts of the low-lying areas. The present study is therefore an attempt to employ the GIS based multi-criterion decision analysis (MCDA) and analytical Hierarchy Process to derive land suitability assessment of Udalguri district for Small Tea Plantations (STPs). Here, 12 factors with the potential to influence land suitability (namely, elevation, slope, groundwater, precipitation, temperature, relative humidity, Soil pH, Soil Nitrogen, Soil Moisture, Soil Organic Carbon, LULC and NDVI) are considered for land suitability assessment of STPs. These criteria are assigned weightages using AHP, wherein elevation has been given the highest criteria followed by groundwater and others. Based on these techniques, land suitability assessment (LSA) of the district is classified into four zones, namely high, moderate, marginal and not suitable. The results, thus validated, imply that the methodology adopted in deriving LSA is highly reliable, which can support the sustainable utilisation, development and management of land resources in the district. Besides the identification and mapping of village wise LSA are very essential for planning of land resource management and agricultural risk mitigation, which ultimately help in sustainable rural development.